Divergent responses of plant multi-element coupling to nitrogen and phosphorus addition in a meadow steppe - Yang Yang; Meini Jin; Jushan Liu (BMC Plant Biology)
Abstract The intricate biogeochemical cycling of multiple elements plays a pivotal role in upholding a myriad of ecosystem functions. However, our understanding of elemental stoichiometry and coupling in response to global changes remains primarily limited to plant carbon: nitrogen: phosphorus (C: N: P). Here, we assessed the responses of 11 elements in plants from different functional groups to global changes. Investigating the stoichiometric ratios and interrelationships of these elements in response to global change is crucial for advancing our understanding of nutrient cycling dynamics in ecosystems. We found that N deposition induced stoichiometric imbalances in Gramineae, leading to a reduction in elemental coupling. This disruption in elemental coupling could potentially affect plant growth and ecosystem functioning. However, leguminous plants, which possess specialized nitrogen fixation mechanisms, were unaffected, suggesting that their ability to independently regulate N may help them maintain stable nutrient ratios despite external N inputs. These findings highlight functional differences among plant groups in their response to global changes, with important implications for ecosystem resilience and nutrient dynamics. In summary, these diverse responses underscore the importance of understanding the underlying mechanisms to be able to better predict the future trajectory of terrestrial biogeochemical cycles under global N enrichment.